Avaliação dos fatores ambientais, sociais e de governança (ESG): uma proposta para universidades federais - Felismino, Marina Miranda (2023)
Environmental, social and governance factors, known in more recent literature as ESG, are becoming increasingly significant for the comprehensive assessment of organizations. It is essential that ESG factors and their metrics be implemented, not only in private companies, but in all public instances, measuring actions to protect the environment, diversity, inclusion, respect for human rights, governance and transparency. In this way, due to the Federal Universities being institutions that promote teaching, research and extension and, therefore, opinion makers, being present in a context with unique relevance, it becomes essential for these institutions to promote the best practices of environmental sustainability, social and governance. In this context, there is a need to find tools that allow monitoring and analyzing the effectiveness of socio-environmental sustainability and governance actions at a Federal University, so that their measurement provides the institution with the necessary information to support the management, control, and planning and carrying out its activities. Thus, this study has the general objective of proposing an evaluative instrument to verify the level of adherence to ESG practices within the scope of Federal Universities. In order to reach the proposed objectives, a field research will be carried out, using the Design Science Research strategy. The proposed instrument was created from a bibliographic review and was validated by conducting interviews with public higher education professionals with knowledge in the area and specialists. This research will make it possible to develop a proposal for an ESG instrument applicable to Federal Universities, providing these institutions with ways to measure progress towards meeting the strategic objectives of socio-environmental sustainability and governance.